Superior Semicircular Canal Dehiscence Syndrome without Vestibular Symptoms - Teixeira,Emidio Oliveira (2014)
Introduction Superior semicircular canal dehiscence syndrome is mainly characterized by vestibular symptoms induced by intense sound stimuli or pressure changes, which occur because of dehiscence of the bony layer covering the superior semicircular canal. Case Report Here, we report a case of the syndrome with pulsatile tinnitus and ear fullness, in the absence of vestibular symptoms. Discussion Signs and symptoms of the syndrome are rarely obvious, leading to the requirement for a minimum workup to rule out or make diagnosis more probable and thus avoid misconduct.